МЕНОНІТИ: ìСВОЇî АБО ìЧУЖІî НА ПІВДНІ УКРАЇНИ (1789ñ1917)? (Zaporizhzhia Historical Review, 2021)
This article is dedicated to the problem whether to consider the Mennonites belonging to the South of Ukraine or strangers there in 1789ñ1917. This problem was analyzed by the author in connection with the issue of identity of the Mennonites.